(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper investigates the profound interconnection between political dynamics and personal experiences in Rohinton Mistry’s Such a Long Journey. Set in the politically volatile era of early 1970s India, the novel captures the pervasive influence of Indira Gandhi’s administration and the looming spectre of the Emergency on the lives of its characters. Focusing on Gustad Noble, a bank clerk whose life is upended by political intrigue and personal betrayal, the analysis delves into how Mistry weaves historical events into the fabric of everyday life. The paper examines the nuanced portrayal of Gustad’s relationships, particularly with Major Jimmy Bilimoria, to illustrate the broader impacts of political corruption and state oppression on individual trust and familial bonds. Themes such as corruption, loyalty, duty, and fear are explored in depth, alongside the novel’s use of symbolism and metaphor to reflect the intrusion of politics into personal domains. Through this exploration, the paper aims to elucidate Mistry’s critique of the socio-political landscape of the time and its reverberations in the personal lives of his characters, demonstrating the inseparable nature of the political and the personal in shaping human experience and identity.